Moving Forward: Recent Developments for the Ferret Biomedical Research Model - Albrecht, Randy A.; Liu, Wen-Chun; Sant, Andrea J.; Tompkins, S. Mark; Pekosz, Andrew; Meliopoulos, Victoria; Cherry, Sean; Thomas, Paul G.; Schultz-Cherry, Stacey (mBio, 2018)
Since the initial report in 1911, the domestic ferret has become an invaluable biomedical research model. While widely recognized for its utility in influenza virus research, ferrets are used for a variety of infectious and noninfectious disease models due to the anatomical, metabolic, and physiological features they share with humans and their susceptibility to many human pathogens. Since the initial report in 1911, the domestic ferret has become an invaluable biomedical research model. While widely recognized for its utility in influenza virus research, ferrets are used for a variety of infectious and noninfectious disease models due to the anatomical, metabolic, and physiological features they share with humans and their susceptibility to many human pathogens. However, there are limitations to the model that must be overcome for maximal utility for the scientific community. Here, we describe important recent advances that will accelerate biomedical research with this animal model.